Difficult air-way path. A case presentation. - José Julio Ojeda González; Evangelina Dávila Cabo de Villa (Medisur)
This paper reports the case of an inpatient from the provincial hospital ¨Dr. Gustavo Aldereguía Lima¨ from Cienfuegos Province that had a difficult access to the air ways. The paper describes the application of the predictive tests as well as the results when using Fastrach, a useful tool that favoured the location of the endotracheal tube of less calibre in this patient.